Playing Easy or Playing Hard to Get: When and How to Attract FDI - Thomas A. Gresik; Dirk Schindler; Guttorm Schjelderup (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the link between a country's institutional quality in tax collection and its optimal corporate tax policies in a model of heterogeneous multinationals that can shift income using both debt and transfer prices. Countries with weak institutional quality can be made worse off adopting policies that attract FDI as the benefits from higher wages and production are more than offset by tax base erosion. Countries with moderate institutional quality can gain from under-utilizing their ability to collect taxes, since the benefit of attracting more FDI outstrips the benefit of increased tax revenue. Countries with very strong institutions benefit from FDI and should utilize their full ability to collect taxes.
Keywords: F23; H26; H32; F68; 330; FDI; thin capitalization rules; transfer pricing; institutional quality